Trade Protection and Industry Wage Structure in Poland - Chor-ching Goh; Javorcik, Beata S. (World Bank, Washington, DC, 2012)
The authors examine the impact of Poland's trade liberalization in 1994-2001 on the industry wage structure. The liberalization was undertaken in preparation for Poland's accession to the European Union and was more pronounced in industries with larger shares of unskilled labor. Their analysis indicates that a decrease in an industry tariff was associated with higher wages being earned by workers employed in the industry, controlling for worker characteristics and geographic variables. The result is robust to including year and industry fixed effects, controlling for industry-level exports, imports, concentration, stock of foreign direct investment, and capital accumulation. The finding is consistent with liberalization increasing competitive pressures, forcing firms to restructure and improve their productivity, which in turn translates into higher profits being shared with workers. It could also be potentially attributed to trade liberalization lowering the costs of imported inputs, which enhances firm profitability. The result holds when skilled workers are excluded from the sample, thus suggesting that reductions in trade barriers benefited the unskilled in terms of an increase in wages.